Implications of large‐scale miscanthus cultivation in water protection areas: A Life Cycle Assessment with model coupling for improved policy support. Issue 11 (8th September 2022) - Weik, Jan; Lask, Jan; Petig, Eckart; Seeger, Stefan; Marting Vidaurre, Nirvana; Wagner, Moritz; Weiler, Markus; Bahrs, Enno; Lewandowski, Iris; Angenendt, Elisabeth
Abstract: Two major global challenges related to agriculture are climate change and the unbalanced nitrogen cycle. For both, national and international reduction targets have been defined to catalyse policy support for more sustainable farming systems. Miscanthus cultivation in water protection areas has been proposed as a contribution to achieving these targets. However, a thorough understanding of the underlying system dynamics at various spatial levels is required before recommendations for policy development can be provided. In this study, a model framework was established to provide economic and environmental indicator results at regional and sub‐regional levels. It presents a consequential Life Cycle Assessment coupled with an agro‐economic supply model (Economic Farm Emission Model) that simulates crop and livestock production, and an agricultural hydrology model (DAISY) that assesses effects on the nitrogen cycle. The framework is applied to Baden‐Württemberg, a federal state in southwest Germany with eight agro‐ecological regions. Scenarios investigating the differences between mandatory and voluntary miscanthus cultivation were also explored. While the results show the high potential of miscanthus cultivation for the reduction of greenhouse gas emissions (−16% to −724%), the potential to reduce nitrate leaching (−4% to −44%) is compromised in some sub‐regions and scenarios (+4% to +13%) by substantial effects on the crop rotation. Furthermore, the cultivation of miscanthus reduces gross margins in most sub‐regions (−0.1% to −9.6%) and decreases domestic food production (−1% to −50%). However, in regions with low livestock density and high yields, miscanthus cultivation can maintain or increase farmers' income (0.1%–5.8%) and improve environmental protection. The study shows that the heterogeneity of arable land requires a flexible promotion programme for miscanthus. Voluntary cultivation schemes were identified as most suitable to capture sub‐regional differences. Policies should address the demand for miscanthus, for example, support the development of regional value chains, including farmers, water suppliers and the biobased industry. Abstract : Miscanthus cultivation in water protection areas has been proposed as a contribution to achieving sustainability targets in the European farming sector. To investigate underlying system dynamics, a model framework (Life Cycle Assessment, Economic Farm Emission Model and agricultural hydrology model) was established to provide indicator results at regional and sub‐regional levels for Baden‐Württemberg. While the results show high potential of miscanthus cultivation for the reduction of greenhouse gas emissions and (in most cases) of nitrate leaching, the gross margins were reduced in most sub‐regions and the domestic food production in all sub‐regions. The study shows that the heterogeneity of arable land requires a flexible promotion programme for miscanthus.